Effectiveness of Novel Drug Delivery System using Curcumin in Alzheimer’s Disease - Aswar, Urmila; Rathod, Kundlik; Mathure, Dyandevi (Central Nervous System Agents in Medicinal Chemistry, 2024)
Alzheimer's disease (AD) is a form of brain degeneration that gradually impairs a person's memory and cognitive skills, eventually making it harder for them to perform everyday activities. Its pathophysiology has been attributed to the deposition of amyloid β (Aβ), neurofibrillary tangles (NFT), and α-synuclein (A-s) in some cases. Presently, 4 drugs have been approved for the treatment. They are Donepezil, Rivastigmine, Galantamine and Memantine. The first three are acetylcholinesterase inhibitors, while memantine is an NMDA receptor antagonist. Even though these medications are successful in treating mild to moderate Alzheimer's disease, they have not been able to reverse the disease or even slow its progression completely. Hence, natural products are gaining more popularity due to the advantage of the multitarget intervention effect. The most investigated spice, Curcuma longa's bioactive component, curcumin, has demonstrated anti-amyloid, anti-NFT, and anti-Lewy body properties and substantial antiinflammatory, antioxidant, and antiapoptotic properties. However, its proven neuroprotective activity is hampered by many factors, such as poor water solubility and bioavailability. Therefore, many novel formulations have been designed to improve its bioavailability with methods such as 1) Micellar Solubilization, 2) Cyclodextrin Complexation, 3) Crystal Modification, and 4) Particle Size Reduction, etc. The current chapter aims to summarize various novel formulations of curcumin and their effectiveness in treating AD.
Keywords: blood-brain barrier